El programa de acreditación nacional para el acceso a los cuerpos docentes universitarios tras la aprobación del Real Decreto 678/2003 - José Luis Moreno Garvayo (Revista Vasca de Administración Pública)
Quality and excellence are two closely related concepts in the field of the evaluation of research activity and the selection of university teaching staff. The approval of the LOSU has forced changes in the system of accreditation and access to university teaching bodies in order to incorporate different innovations, focused on key elements such as which profiles must be accredited, how the composition of the different commissions in charge of the evaluation is regulated and, especially, which criteria and merits are required to obtain a favorable resolution. In this paper we offer an overview of ANECA¿s new accreditation program that emerged after the approval of Royal Decree 678/2023, of July 18; as well as of the merits and competencies that can be evaluated, which follow the guidelines of the international movement for the reform of research evaluation.